Tachycardiomyopathy: long-term sequelae of arrhythmia-induced acute heart failure. (3rd October 2022) - Stronati, G; Urbinati, A; Brugiatelli, L; Alfieri, M; Bastianoni, G; Casella, M; Dello Russo, A; Guerra, F
Abstract: Introduction: The definition of heart failure (HF) is known to include different etiological entities which may lead to the plethora of signs and symptoms characteristic of the syndrome. When it comes to HF with reversible forms of reduced ejection fraction (EF), tachycardiomyopathy (TCM) accounts for around 10% of all hospitalizations for acute HF. Among the TCM group we can identify situations in which an arrhythmia is the sole cause for the reversible cause of LV (pure TCM), and cases in which LV deterioration is mediated by the arrhythmia, on a substrate of diseased heart. Purpose: The aim of our study was to investigate the prognosis of patients with pure and impure TCM compared to patients with ischemic HF and idiopathic HF. Methods: We conducted and observational prospective study enrolling all patients who were admitted with a diagnosis of de novo acute HF with reduced EF between January 2012 and June 2020. All patients were divided into four groups based on guideline-specific definitions: structural HF (encompassing ischemic, valvular, inflammatory, and infiltrative causes, as well as hypertrophic and arrhythmogenic cardiomyopathy), idiopathic HF, pure TCM and impure TCM. Patients presenting with a decline in EF due to any kind of tachyarrhythmia and a subsequent recovery of left ventricular EF after rhythm or rate control were diagnosed with TCM. Further grouping into pure or impure was made according to the presence of absence of underlying heart disease. Results: 456 patients were consecutively enrolled (304 males, 70±13 years). The four groups had significantly different estimates for all-cause death, with pure TCM having the highest survival and structural HF having the lowest over a median 6-year follow-up (pure TCM 22.1%; impure TCM 32.1%; idiopathic HF 26.3%; structural HF 51.9%; log-rank p<0.0001; Figure 1a). Using structural HF as a comparator, HRs for death were significantly lower for all the other three groups (pure TCM HR 0.35; 95% CI 0.21–0.57; impure TCM HR 0.48; 95% CI 0.24–0.96; idiopathic HF HR 0.53; 95% CI 0.31–0.90). Unplanned hospitalizations showed a different trend, with TCM having the highest rate and non-ischemic HF having the lowest over the same follow-up (pure TCM 58.1%; impure TCM 40.2%; idiopathic HF 15.8%; structural HF 38.4%; log-rank p<0.0001; Figure 1b). The average total number of unplanned hospitalizations also differed significantly between the four groups (pure TCM 0.84; 95% CI 0.65–1.04; impure TCM 0.88; 95% CI 0.53–1.23; idiopathic HF 0.45; 95% CI 0.25–0.65; structural HF 1.02; 95% CI 0.78–1.25; p=0.021). Conclusions: Among all patients with de novo acute HF, those who present structural heart disease present a lower survival rate over a 6-year follow up. However, patients with pure TCM present the highest rate of unplanned hospitalizations when compared to the other groups. It is therefore important to identify the etiology of HF to start appropriate treatment and prevent new hospitalizations. Funding Acknowledgement: Type of funding sources: None.